Contamination of hospital food with Clostridium difficile in Central Italy. (February 2019) - Primavilla, Sara; Farneti, Silvana; Petruzzelli, Annalisa; Drigo, Ilenia; Scuota, Stefania
Abstract: This study investigates the contamination of foods with Clostridium difficile in 3 hospitals of Central Italy. We used real-time PCR for tpi gene to analyse 350 food samples, including 296 cooked meals and 54 foods to be eaten raw. The molecular screening test was positive for 3 samples, but toxigenic C. difficile was isolated only in two of them. The prevalence in cooked food was 0, 3% (1/296), while in uncooked processed foods was 1, 9% (1/54). Data support the potential risk of food as a source of toxigenic C. difficile for hospitalized patients, but further investigations are needed. Highlights: 1 350 food samples from three Italian hospitals were investigated for C. difficile . 2 The overall prevalence of C. difficile-positive hospital meals was 0, 6% (2/350). 3 Both the isolated strains were toxigenic.